Knowing a Rape Victim, Personal Sexual Victimization Experience, and Gender Predicting Rape Victim Empathy - Osman, Suzanne L. (Victims & offenders, 2023)
Empathy with a rape victim was examined based on knowing a rape victim (not oneself), personal sexual victimization experience, and participant gender. Undergraduates (n = 531) at a midsize public university in the Northeast United States completed the Rape-Victim Empathy Scale, the Sexual Experiences Survey-Short Form Victimization, and questions regarding knowing a rape victim. Empathy scores were greater for those who reported knowing a rape victim than for those who did not. Women with personal sexual victimization experience reported greater empathy than men with personal sexual victimization experience and all nonvictims, but no differences emerged among female nonvictims and all men. Findings suggest that knowing a rape victim may provide some degree of vicarious experience with rape that helps individuals better understand a rape victim’s perspective, and factors influencing rape empathy among men and nonvictims needs more attention in future research.